Using agile methods for the development of green and sustainable software: Success factors for GSD vendors. Issue 8 (19th December 2017) - Rashid, Nasir; Khan, Siffat Ullah
Abstract: Over the last decade, the use of agile methods has grown dramatically for software development. Agile methods guarantee to accelerate the delivery of remarkable software with increased user satisfaction and reduced cost. However, in recent years, due to the emergence of green software engineering, software developers are compelled to focus more on green and sustainable aspects of software. Green software engineering aims to design, develop, and use the software with confined energy and computing resources. Recently, software engineers in global software development have adapted agile methods for quick, interactive, and environment‐friendly software development. In this study, we have identified 16 success factors, through systematic literature review (SLR) and applied contrived search criteria derived from the research questions; 80 relevant papers were identified and reviewed. Findings of the SLR study were then empirically validated through questionnaire survey in global software development industry, in which 106 experts from 25 different countries participated. The findings of our industrial survey are mostly in coherence with the SLR findings. However, there is a difference in ranks of the various success factors across the 2 data sets (SLR and industrial survey).